EVALUATION OF THE EFFICIENCY OF DECARBONIZATION INVESTMENTS IN THE OIL AND GAS INDUSTRY - Vytvytska, Uliana (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article considers the methodology for evaluating the effectiveness of investment projects for decarbonization in the oil and gas industry. It is determined that in today’s conditions, low-carbon development is the basic strategy of sustainable development of any country, which combines priorities in the field of climate change and national economic development. Oil and gas companies also have significant greenhouse gas emissions, especially during the development of oil and gas fields, and they are also relevant to the implementation of investment projects to reduce harmful emissions through decarbonization. A methodological approach has been proposed, which allows to take into account the time factor at the main stages of the life cycle of investment projects for decarbonization: in the period of investment costs, payback period and operating period. For each period, the features of determining the net economic profit, direct environmental benefits of the investor and indirect environmental benefits that may arise from third parties as a result of the investment project on decarbonization with adjustment factors that allow to take into account both positive and negative environmental impacts. It has been also proposed to apply the appropriate procedures for taking into account the time factor for each of the periods: compounding - during the design, purchase of equipment and construction of the necessary facilities; discounting - in the payback period and the main operating period. The method of establishing income norms for compounding and ecological discount rates when applying the discounting procedure has been determined. A model for evaluating the effectiveness of decarbonization investments in oil and gas production has been proposed. Further research should focus on improving methodological approaches to identifying the most important factors that cause risks of potential greenhouse gas emissions in specific oil and gas fields, and appropriate environmental discount rates that allow these risks to be taken into account when assessing the effectiveness of decarbonisation investment projects.